Synergy Modeling of Microfinance Institutions in Bali's Pekraman Villages - Ida I Dewa A Yayati Wilyadewi (Yayasan Ilomata, 2026)
Microfinance institutions (MFIs) play a strategic role in supporting grassroots economic development, yet increasing competition in the financial services sector and restrictive credit regulations have placed significant pressure on their sustainability. In Bali the Lembaga Perkreditan Desa (LPD) has historically demonstrated effectiveness in fostering development within traditional villages, but currently faces challenges similar to other MFIs. This study examines how institutional synergy can serve as a solution to overcome competitive constraints, with the main research question focusing on how a standardized synergy model among MFIs can be developed and implemented to strengthen LPD sustainability. The study employs a qualitative case-based modeling approach, drawing on supporting theoretical frameworks, in-depth interviews with the LPD of Kedonganan Traditional Village, and the researcher’s analytical interpretation. The data were synthesized to develop a practical synergy model grounded in interview evidence and document review, with interpretive steps made explicit through coding procedures and triangulation. The findings indicate that structured synergy among MFIs can reduce competitive friction, enhance institutional resilience, and expand development-oriented financial services. The proposed model demonstrates practical feasibility and adaptability for broader implementation across LPDs in Bali. This research concludes that institutional synergy represents a viable strategy for strengthening LPDs as microfinance institutions and accelerating sustainable economic development in Bali Province. The main implication is that collaborative rather than competitive institutional frameworks can enhance the long-term effectiveness of community-based financial institutions.